Efektivitas Model Pembelajaran TSTS (Two Stay Twi Stray) untuk Meningkatkan Pemahaman Konsep pada Materi Sistem Pernapasan Manusia Siswa Kelas VIII SMPN 06 Pekanbaru - Sari, Vivi Novita; Arni, Gita Maya; Yusmeinur, Yusmeinur; Yolanda, Resti (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to assess the effectiveness of the Two Stay Two Stray (TSTS) model in enhancing conceptual understanding of the human respiratory system among eighth-grade students at SMP N 6 Pekanbaru during the academic year 2011/2012. Employing a pretest-posttest control group design, the study sampled 64 students using purposive random sampling techniques. Parameters were evaluated through pretests, posttests, and observation sheets. Data analysis utilized paired sample t-tests, revealing an average N-gain of 0.23 in the control group (categorized as low) and 0.33 in the experimental group (categorized as moderate). The findings indicate that employing the TSTS model effectively enhances students' learning outcomes regarding the human respiratory system concept in the eighth grade. These results underscore the significance of innovative teaching methodologies, such as TSTS, in fostering deeper conceptual understanding and academic achievement in science education.